INDONESIAN DIPLOMACY IN ACHIEVING ECONOMIC INTEREST: THE POTENTIAL OF HALAL TOURISM IN WEST NUSA TENGGARA ON PERIOD 2013-2016 - rachmadhana allifa maulana (: 2621-0924)
This research aimed for revealing the role of halal tourism in West Nusa Tenggara as one form of Indonesian public diplomacies for increasing the number of foreign tourists which directly affects the increase of income of Indonesian foreign exchange. This research is built through two approaches: the concept of public diplomacy and the concept of national interest. This research uses qualitative method that consists of interview, literature review and observation which is related to the topic to answer the problem formulation. Technique of data analysis used in qualitative research includes transcripts of interview result, data reduction, data analysis and interpretation. Employing the concept of public diplomacy, this research can reveal the role of halal tourism in West Nusa Tenggara as a form of Indonesian diplomacy on the increase of foreign tourists. Meanwhile, using the concept of national interest, it can explain the influence of halal tourism in West Nusa Tenggara on the economic goals of Indonesia. The suggestion of this research is, the Tourism Government of West Nusa Tenggara should manage and exploit the potential of Halal tourism in West Nusa Tenggara more intensively in order to achieve better results.Keywords: halal tourism, West Nusa Tenggara, public diplomacy, economic interest